Bibliometric insights into the most influential papers on antibiotic adjuvants: a comprehensive analysis - Sun, Ke; Xu, Ping; Zhang, Yu; Yu, Pingjing; Ju, Yuan (Frontiers in Pharmacology, 2023)
Background: The utilization of antibiotic adjuvants presents a promising strategy for addressing bacterial resistance. Recently, the development of antibiotic adjuvants has attracted considerable attention from researchers in academia and industry. This study aimed to identify the most influential publications on antibiotic adjuvants and elucidate the hotspots and research trends in this field. Method: Original articles and reviews related to antibiotic adjuvants were retrieved from the Web of Science Core Collection database. The top 100 highly cited publications were selected and the visual analyses of publication outputs, countries, institutions, authors, journals, and keywords were conducted using Excel, VOSviewer, or CtieSpace software tools. Results: The top 100 cited publications concerning antibiotic adjuvants span the years 1977 to 2020, with citation counts ranging from 174 to 2735. These publications encompassed 49 original articles and 51 reviews. The journal “Antimicrobial Agents and Chemotherapy” accounted for the highest number of publications (12%). The top 100 cited publications emanated from 39 countries, with the USA leading in production. Institutions in Canada and the USA exhibited the most substantial contributions to these highly cited publications. A total of 526 authors participated in these studies, with Robert E.W. Hancock, Laura J. V. Piddock, Xian-Zhi Li, Hiroshi Nikaido, and Olga Lomovskaya emerging as the most frequently nominated authors. The most common keywords included “E. coli”, “P. aeruginosa”, “S. aureus”, “in-vitro activity”, “antimicrobial peptide”, “efflux pump inhibitor” “efflux pump”, “MexAB-OprM” and “mechanism”. These keywords underscored the hotspots of bacterial resistance mechanisms and the development of novel antibiotic adjuvants. Conclusion: Through the bibliometric analysis, this study identified the top 100 highly cited publications on antibiotic adjuvants. Moreover, the findings offered a comprehensive understanding of the characteristics and frontiers in this field.